Designing New Block Cipher Based On Genetic Algorithm Approach - Nur Hafiza Binti Zakaria; Ramlan Mahmod; Nur Izura Udzir; Zuriati Ahmad Zukarnain; Suriyani Ariffin (International Journal of Computer Science and Information Security, 2024)
Non-Indexed Publication